An empirical analysis of the dimensions of corporate social responsibility in Portugal - Afonso, Sandra Cristina (2012)
This paper investigates factors that can explain the motivations of Portuguese companies to a social performance. The study was based on a sample of nineteen large Portuguese companies, listed on the PSI 20 index, for a period of five year, since 2005 to 2009. A Factorial Analysis was applied to identify the dimensions of Portuguese Corporate Social Responsibility using variables reference on the Green Book of European Community Commission (ECC, 2001). The results produced two dimensions that may explain Portuguese corporate motivation social performance: (1) Standards and Legal Requirements and (2) Ethic and social conduct. Further research may be done to find correlations with these dimensions and financial and economic corporate performance.